A Real‐Time Wearable UV‐Radiation Monitor based on a High‐Performance p‐CuZnS/n‐TiO2 Photodetector. Issue 43 (30th August 2018) - Xu, Xiaojie; Chen, Jiaxin; Cai, Sa; Long, Zhenghao; Zhang, Yong; Su, Longxing; He, Sisi; Tang, Chengqiang; Liu, Peng; Peng, Huisheng; Fang, Xiaosheng
Abstract: Solar radiation, especially ultraviolet (UV) light, is a major hazard for most skin‐related cancers. The growing needs for wearable health monitoring systems call for a high‐performance real‐time UV sensor to prevent skin diseases caused by excess UV exposure. To this end, here a novel self‐powered p‐CuZnS/n‐TiO2 UV photodetector (PD) with high performance is successfully developed (responsivity of 2.54 mA W −1 at 0 V toward 300 nm). Moreover, by effectively replacing the Ti foil with a thin Ti wire for the anodization process, the conventional planar rigid device is artfully turned into a fiber‐shaped flexible and wearable one. The fiber‐shaped device shows an outstanding responsivity of 640 A W −1, external quantum efficiency of 2.3 × 10 5 %, and photocurrent of ≈4 mA at 3 V, exceeding those of most current UV PDs. Its ultrahigh photocurrent enables it to be easily integrated with commercial electronics to function as a real‐time monitor system. Thus, the first real‐time wearable UV radiation sensor that reads out ambient UV power density and transmits data to smart phones via wifi is demonstrated. This work not only presents a promising wearable health monitor, but also provides a general strategy for designing and fabricating smart wearable electronic devices. Abstract : A real‐time wearable UV sensor for prevention of skin cancers caused by excess UV radiation exposure is demonstrated. The fiber‐shaped device consisting of a novel p‐CuZnS/n‐TiO2 nanotube array structure exhibits an outstanding photocurrent and external quantum efficiency, a fast response speed, and self‐powered property, which make it a promising wearable real‐time health monitor.